Pastoral options for minority communities applied to the Archdiocese of Wellington. - O'Sullivan, Anthony Bernard. (University of Ottawa (Canada), 1999)
This canonical study explores the options open to a diocesan bishop for the provision of pastoral cue to people who do not readily find a place in the local parish. Particularly since the migrations from Europe to North America towards the end of the nineteenth century, the Roman Catholic Church bad established parishes for the various language groups as alternatives to the territorial parishes which were largely English-speaking. In 1952 Pope Pius XII's Exsul familia offered a further option called the "mission with care of souls" which allowed for greater flexibility. Since the Second Vatican Council, what was initially developed as migrant legislation now finds a broader application for any group which finds itself unable to benefit from the ordinary pastoral care offered by the territorial or local parish. In 1965 the Decree on the Pastoral Office of Bishops offered the following for Pastoral care, which it particularly applied to people on the move: "Special concern should be shown for those among the faithful who, on account of their way or condition of life, cannot sufficiently make use of the common and ordinary pastoral services of parish priests or are quite cut off from them. Among this group are very many migrants, exiles and refugees, seamen, airplane personnel, gypsies, and others of this kind." This solicitude now finds expression in c. 383 of the 1983 Code of Canon Law, where it no longer applies exclusively to migrant groups: "In exercising his pastoral office, the diocesan Bishop is to be solicitous for all Christ's faithful entrusted to his care, whatever their age, condition or nationality, whether they live in the territory or are visiting there. He is to show an apostolic spirit also to those who, because of their condition of life, are not sufficiently able to benefit from ordinary pastoral care, and to those who have lapsed from religious practice." Chapter One presents the European and North American context from which the law on parishes and the pastoral care of migrants has come. Chapter Two explores various papal, curial and Vatican Council documents from this century in which the law has been presented and applied. Documents since the Council, including the 1983 Code, have applied and fleshed out the cultural insights of the council. Chapter Three details the New Zealand context in which the law and people from Europe meet the people from the Pacific. Chapter Four applies the law to the New Zealand situation. It weighs the options of personal parish, quasi-parish, and chaplaincy within the territorial parishes for meeting the pastoral needs of the two sample groups of the indigenous Maori, and Samoan migrants and their descendants. The author concludes that the personal parish respects the freedom and rights of minority groups, and allows for integration from a position of strength.
Keywords: Religion, General.